Transnational Khmer cultural landscapes: A comparative analysis of symbols, belief systems, and communal structures in Vietnam, Cambodia, Thailand, and Laos - Ca, Nguyen Minh; Diem, Nguyen Thuy; Pham, Hang Thu (Edelweiss Applied Science and Technology, 2025)
This article presents a cross-national comparative study of the cultural symbols of the Khmer people in Vietnam, Cambodia, Thailand, and Laos—framing them as a transborder semiotic network that operates beyond the confines of nationality and territory. Drawing on the theoretical frameworks of cultural semiotics (Barthes, Lotman), ritual theory (Turner), and collective memory (Assmann), the study proposes a three-tiered model of symbolic analysis encompassing the visual, functional, and mnemonic dimensions. Data were collected through fieldwork, in-depth interviews, and participant observation in Sóc Trăng and Trà Vinh (Vietnam), Phnom Penh (Cambodia), Surin (Thailand), and Champasak (Laos), and were analyzed using multi-level semiotic and structural comparison methods. The findings reveal that in Cambodia, the Khmer symbolic system has been nationalized as a cornerstone of national identity. In contrast, in Vietnam, the Khmer community serves as a soft agent of indigenization, reviving and maintaining symbolic forms through rituals, temples, language, and performative practices. Meanwhile, in Thailand and Laos, Khmer symbols have been largely assimilated, simplified, or excluded from public representation. The article proposes a new approach to minority identity studies in regional contexts and highlights the unique intermediary role of the Vietnamese Khmer within the cultural architecture of Southeast Asia.